The effectiveness of a dedicated central venous access care team to prevent catheter-related bloodstream infection in a private hospital - Cybele L. Abad; Jia An G. Bello; Maria Jesusa Maño; Fortune Charles V. de Lara; Ma. Cristina P. Perez (Elsevier, 2023)
Summary: Objective: We hypothesized a dedicated team would decrease catheter-related bloodstream infection (CRBSI) rates. Method: We implemented a before-after study. Results: CRBSI frequency (39/103 vs. 28/105, P=0.084) and incidence (36.61/1000 vs. 26.1/1000 catheter-days, P=0.175) were lower in the intervention arm. Conclusion: The intervention delayed median time to CRBSI, but was insufficient to decrease overall rates.